On context dependence of behavioral variability in inter-personal coordination - Oullier, O.; de Guzman, G.C; Jantzen, K.J.; Kelso, J.A.S. (International Journal of Computer Science in Sport, 2002)
Results from recent studies investigating the dynamics of bimanual coordination have led to contrasting viewpoints concerning the relative contribution of perceptual and motor processes in mediating coordinative stability. At one end of the spectrum is the belief that coordination is governed primarily by physical limitations such as neuro-muscular constraints and that perceptual factors play little role (Carson, 2004). At the other end, the stability of bimanual coordination is depicted as completely arbitrary with respect to the physical properties of the individual components, depending instead only on the directional and visuo-spatial relationship between them (Mechsner, 2004).